Pengaruh Kompleksitas Tugas, Etika Profesi dan Struktur Audit Terhadap Kinerja Auditor - Primayeta Wahyuni; Dewi Zulvia (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine task complexity, professional ethics and audit structure on auditor performance. Collecting research data using a questionnaire. The questionnaire was submitted to the Public Accounting Office in Padang City. This research is included in quantitative research. The sample was determined using a purposive sampling technique. Data analysis uses multiple regression using SPSS 22 software. The results of this research show that Task Complexity has a positive effect on Auditor Performance, Professional Ethics has a positive effect on Auditor Performance and Audit Structure has no effect on Auditor Performance.